GEOCHEMISTRY AND MINERALOGY OF THE CHROMITE ORES FROM CHOMAN AREA (NORTHERN IRAQ) - BARZANI, HAWAR Y. (Fırat Üniveristesi, 2019)
İncelenen Çoman Bölgesi kromitleri Zagros Suture Zonu üyesi Walash Grubu ofiyolitik kayaçları içinde bulunmaktadır. Kromit kütleleri massif, kırıklı ve sürüklenme izleri taşırlar. Cevher dokusu genellikle massif ve az olarakta saçınımlıdır. Cevher mineralleri kromit (baskın), manyetit, pirotin, Ni-Co sülfidler ve pentlandittir. Kromit taneleri plivin, spinel, Ni-Co Sülfidler, vanadium ve kalsit inclusionları içermektedirler. Ana kayaç tamamen serpantinleşmiştir ve türleri ancak jeokimyasal verilerle lerzolit ve harzburjit olarak saptanabilmiştir. Kromitlerin ana bileşim kompozisyonları fazla değişmemektedir: (ağırlık yüzdesi olarak) Cr2O3: 36-53, Fe2O3: 11-20, Al2O3: 5-8, MgO: 11-17. Hemen bütün örneklerde Cr/Fe oranı 2.5 tan fazladır ki bu oran kromit cevher pazarında ana parametrelerden biridir. Tüm jeokimyasal veriler incelenen kromitlerin Alpin Tipi ve Alumuna kromit olduğunu göstermektedir. Jeokimyasal veriler kromitlerin Boninit fore arc bölgesinde geliştiğini göstermektedir. Altere kromitler supra subduction ortamı jeokimyasal verilerine sahiptir. Anahtar Kelimeler: Kromit, Çoman Bölgesi, ofiyolit, kromit jeokimyası.

Chromites formations of Choman District, NE Iraq, are constituents of ophiolitic rocks of Zagros suture zone and Walash Group. The chromite bodies are massive, highly fractured and bear traces of extensive tectonic movements. Ore textures are dominantly massive, and in places, disseminated ore is also present. Chromites ore minerals are; chromites, magnetite, pyrrhotite, Ni-Co sulphides, pentlandite. Chromite grains bear inclusions of olivine, spinel, Ni-Co sulphides, pyrrhotite, vanadium and calcite. The host rocks are completely serpentinized, and original dominant ultrabasic rocks estimated as lherzolite and harzburgite evaluating whole-rock analytical values. Composition of the chromites do not vary much, and main constituents are (as a weight percentage) Cr2O3: 36-53, Fe2O3: 11-20, Al2O3: 5-8, MgO: 11-17. In almost all the samples Cr/Fe ratio is greater than 2.5, which is the basic parameter in chromite ore market. On the basis of all geochemical indicators for chromite classification graphics, geochemical values of studied chromites fall in Alpine type chromite area and Aluminian Chromite area. Studied chromites have the geochemistry of boninite and fore-arc field parameters. Some data fall to the border of the fore-arc field; this is due to alteration of chromite and increased Cr#, and this result is an indicator of the supra-subduction environment. Keywords: Chromite, Choman District, ophiolite, chromite geochemistry
Çoman bölgesi (Kuzey Irak) kromit cevherleşmenin minerolojisi ve jeokimyasi
Keywords: Jeoloji Mühendisliği